Analisis Pengaruh Promosi dan Physical Evidence dalam Meningkatkan Minat terhadap Jumlah Siswa Baru pada MIM Tamiang Lembah Melintang - Ainil Darti; Yuwarman Mansur (ARZUSIN, 2026)
Although promotion and physical evidence have been widely studied in educational service marketing, studies that specifically analyze the effect of these two variables on public interest in choosing Madrasah Ibtidaiyah Muhammadiyah (MIM) Tamiang Lembah Melintang remain limited. This study aims to analyze the effect of promotion and physical evidence on public interest related to increasing the number of new students at MIM Tamiang Lembah Melintang. This study used a quantitative approach with an explanatory survey design and involved 90 respondents selected through simple random sampling. Data were collected through questionnaires and documentation and were then analyzed using multiple linear regression with the assistance of the Statistical Package for the Social Sciences (SPSS). The results showed that, partially, promotion had no significant effect on public interest, whereas physical evidence had a positive and significant effect on public interest. Simultaneously, promotion and physical evidence had a significant effect on public interest in choosing the madrasah. These findings strengthen the concept of the service marketing mix, particularly the role of physical evidence in shaping public perceptions of the quality of educational services. The conclusion of this study affirms that improving the quality of madrasah facilities and physical environment needs to be a priority in the marketing strategy of educational institutions. The implications of this study include theoretical contributions to the development of educational service marketing studies as well as practical contributions for madrasah administrators in designing more effective marketing strategies to increase public interest and the number of new students.